Studi Keterbacaan dan Nilai Karakter pada Buku Siswa Kelas IV SD (Edisi Revisi 2017) Kurikulum 2013 - Permataningrum, Fazrina Apriliyani; Iswara, Prana Dwija; Karlina, Dety Amelia (Jurnal Pena Ilmiah, 2021)
The readability and value of the character are important factors of the preparation of teaching materials. The method used is a qualitative method with a documentation study approach. The subjects used were the reading texts contained in the fourth-grade elementary school as many as 40 reading texts from 9 themes with the form of a Raygor graph formula. There are 23 reading texts or (57.5%) as appropriate and 17 reading texts or (42.5%) as inappropriate for the level of fourth-grade elementary school. Then, there are 7 reading texts or a small portion (17.5%) containing the value of religious, 21 reading texts or most (52.5%) have Nationalist values, 25 reading texts or most of them (62.5%), contain Mandiri values, 15 reading texts or almost half of them (37.5%) have the value of the Gotong Royong. Lastly, 9 reading texts or a small portion (27.5%) containing the value of the Integrity.